Utilizing Interactive Mobile Technology for Health Education: Creation and Evaluation of a Calorie and Nutrition Tracking Application For The Malaysian Population - Sarni Suhaila, Rahim; Hoe Wai, Chan; Shahril, Parumo; Rosleen, Abdul Samad; Suriati Khartini, Jali (Little Lion Scientific, 2025)
This study investigates the transformative capacity of interactive mobile technology as creative tools for revitalizing health education, highlighting their potential to enhance user understanding and promote greater engagement. This article assesses a detailed calorie and nutrition tracking mobile application designed exclusively for the Malaysian demographic. The main aim of this study was to furnish clients with precise and thorough information regarding their nutritional intake, enabling informed dietary and health decisions. The program comprised multiple components, including user registration, a food database and logging system, goal setting and progress tracking, instructional resources, and a mindfulness evaluation. Contemporary calorie and nutrition tracking programs are predominantly designed for users beyond Malaysia and have a limited database of Malaysian food items, making them less relevant to the local populace. This study focused mostly on Malaysian who wanted to track their calorie consumption for weight loss, muscle development, or weight stabilization. The efficacy of the application as a novel instrument for enhancing dietary control and fostering healthy eating practices was assessed through extensive testing with a representative cohort of Malaysian users. Preliminary findings demonstrate that mobile content significantly improves knowledge and awareness, presenting it as a dynamic, engaging, and accessible medium for disseminating information. This effort utilized mobile technologies to improve food knowledge and health outcomes in Malaysia.